A Comparation Of Chinese And Indonesian Time Adverbs - Ying, Yi (Lingua Cultura, 2012)
Chinese time adverbs describe status of behavior, modal frequency, or that the behavior hasÂ occurred, occurred in the past, present or future. When describe a time, it usually emphasizes theÂ meaning. Indonesian time adverbs describe an event or action occurred at a time. It indicates theÂ status of behavior, modal or indicates whether the conduct has occurred, has not happened, willÂ happen, repeat and describe the act or thing is not yet completed. This study attempts to shed light onÂ why students incline to make mistake in using Chinese time adverbs. Furthermore, students faceÂ difficulty in differentiating between Chinese and Indonesian time adverbs. Chinese Indonesia have theÂ similar meaning of time adverb, such as: gang, yijing, cengjing, zhengzai, jiang, hai, mashang butÂ function in a sentence not exactly same.